Determinants of Employee Punctuality. - Dishon-Berkovits, Miriam; Koslowsky, Meni (Journal of Social Psychology, 2002)
Although researchers have studied employee lateness empirically (e.g., S. Adler & J. Golan, 1981; C. W. Clegg, 1983), few have attempted to describe the punctual employee. In the present study, results of a discriminant analysis on employees in Israel indicated that a personality characteristic, time urgency, a subcomponent of Type A behavioral pattern, distinguished between punctual and late employees. Organizational commitment and age of employee's youngest child also distinguished between the groups. Reprinted by permission of the publisher.